Application of prolonging small feeding volumes early in life to prevent of necrotizing enterocolitis in very low birth weight preterm infants - Qiu-fang Li; Hua Wang; Dan Liu; Yi Tang; Xin-fen Xu (Elsevier, 2016)
Objective: To study the effects of prolonging small feeding volumes early in life on the incidence of necrotizing enterocolitis (NEC) in very low birth weight (VLBW) preterm infants. Methods: A total of 128 VLBW infants who could not be breastfed were assigned into the experimental group (63 cases) and the control group (65 cases) using a random number table. The experiment group was fed 12 mL/(kg·d) on day 1 which was increased to 24 mL/(kg·d) for the first 10 study days. The control group was fed 12 mL/(kg·d) for the first 14-48 hours. Then, the feeding volume increased by 24-36 mL/(kg·d) up to 140-160 mL/(kg·d) and maintained until the 10th day after birth. The incidence of feeding intolerance and NEC, duration of hospitalization, time to full enteral feedings, incidence of intrahepatic cholestasis, and the levels of gastrin and motilin in serum were assessed. Results: The incidence of feeding intolerance was significantly lower in the experimental group compared with the control group (15.87% vs. 33.84%). There was a significant reduction in the incidence of NEC between the experimental and control groups (7.9% vs. 16% in the control group). Conclusion: A protocol that prolongs small feeding volumes early in life can reduce the incidence and severity of NEC, but still warrants further study. Keywords: Infant formula, Necrotizing enterocolitis, Preterm infant, Prolonging small feeding volumes, Very low birth weight infant